Three-pion-exchange potential - Pupin, J. C. (World Scientific Publ Co Pte Ltd, 2003)
Using the chiral symmetry, we calculated the dominant contribution to the nucleon - nucleon potential due to the exchange of three non-correlated pions. This contribution is isovetor with pseudoscalar and axial components. The pseudoscalar component is dominant, it has a range of 1.0 fm and it contributes in the pion channel.